Biometrics Iris Recognition And Two-Factor Authentication For Login System - Noor Shakirin Binti Shaari; Dalilah Abdullah (Journal of Computing Technologies and Creative Content, 2025)
Traditional username and password authentication were easily compromised and had caused a breach of data. Research shows that two-factor authentication and biometrics applied to web systems is a more secure method compared to the traditional username and password when used appropriately. The project was to implement a secure login authentication mechanism for the inventory system in two different environments, the desktop environment, and the mobile browser environment. The stated mechanism is biometric iris detection and two-step authentication using one-time password (OTP).